2009
DOI: 10.1111/j.1708-8208.2009.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Mandibular Ramus Volume as a Source of Bone Grafting

Abstract: The mandibular second molar area provided the thickest cortical graft. A cortical plate of 2.8 mm in average at combined second and third molar areas provided 2.5 mL particulated volume. The use of a design software program can improve surgical treatment planning prior to ramus bone grafting. The AutoCAD software program did not overestimate the volume of bone that can be safely harvested from the mandibular ramus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 22 publications
4
58
0
3
Order By: Relevance
“…2) were entered into a software program †† . Volumetric calculations were performed using a mapping technique described previously 4,5 . Briefly, cross‐sectional images were imported into the program and each 1‐mm cut was mapped by a polyline at the donor site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) were entered into a software program †† . Volumetric calculations were performed using a mapping technique described previously 4,5 . Briefly, cross‐sectional images were imported into the program and each 1‐mm cut was mapped by a polyline at the donor site.…”
Section: Methodsmentioning
confidence: 99%
“…Various surgical techniques have been developed to reconstruct sufficient ridge height and width for functional and esthetic implant therapy. The mandibular symphysis and ramus are good sources of bone grafting 4,5 . Autogenous block grafting from intraoral sites is a predictable technique for successful reconstruction of ridge defects 6 .…”
mentioning
confidence: 99%
“…For the evaluation of bone grafts, measurements of bone volume, height, width, and density have been used to conclude on the fate of the grafted bone [6,12]. Studies have reported on successful bone healing based on bone density information retrieved from CBCT-based data [13], but density values can be questioned due to distortion of Hounsfield Units (HU) in CBCT imaging, i.e., scanned regions of the same density in the skull can have different gray scale values in the reconstructed CBCT data set [14].…”
Section: Introductionmentioning
confidence: 99%
“…Del punto de vista biológico, la mejor opción reconstructiva está en el hueso autógeno (Deatherage;Olate et al, 2007a), existiendo algunas opciones intraorales que pueden ser utilizadas para retirar el hueso necesario; de entre ellos, la rama de mandíbula (Verdugo et al, 2009) y la sínfisis mandibular (Montazem et al, 2000) han sido popularizados por su capacidad de entregar amplias cantidades que permiten injertar en sitios que requieren instalación de implantes o reparar fisuras alveolares.…”
Section: Introductionunclassified